(untitled) (Indonesian Journal of Cultural and Community Development, 2024)
General Background: Clear organizational goals are essential for companies, as they aim to generate profits, benefit stakeholders, and enhance their overall value. Specific Background: The value of a company serves as an indicator of its condition and success, reflecting investor perceptions, especially within the telecommunications sector in Indonesia. Knowledge Gap: Despite existing literature on factors influencing company value, there is limited research specifically addressing the interplay of company size, capital structure, and profitability in the telecommunications industry in Indonesia. Aims: This study aims to analyze the impact of company size, capital structure, and profitability on the value of telecommunications companies listed on the Indonesia Stock Exchange from 2018 to 2022. Results: Utilizing secondary data from annual financial reports and a sample of 10 telecommunications companies, the research employed multiple linear regression analysis, classical assumption testing, and hypothesis testing. The findings reveal that company size does not significantly influence company value, while capital structure and profitability also demonstrate an insignificant impact. Novelty: This research contributes to the understanding of factors affecting company value in the Indonesian telecommunications context, highlighting nuances that may differ from other sectors. Implications: The results suggest a need for further exploration of additional variables that may influence company value, emphasizing the complexity of financial metrics within the telecommunications industry. Highlights: • Lack of Significant Influence: The study found that company size, capital structure, and profitability do not significantly impact company value in the telecommunications sector. • Focus on Telecommunications Sector: This research specifically addresses a gap in literature regarding the telecommunications industry in Indonesia, offering insights that may differ from other sectors. • Need for Further Research: The findings highlight the necessity for exploring additional variables that could affect company value, underscoring the complexity of financial metrics within this industry. Keywords: Company Value, Telecommunications, Capital Structure, Profitability, Indonesia